Empowering the self: Flow state in The Legend of Zelda: Breath of the Wild and Tears of the Kingdom - Schriefer, Natalie (Journal of Gaming & Virtual Worlds, 2026)
Keywords: Creativity; Flow (mathematics); Identification (biology); Legend; State (computer science); Tears; dept.hhs

Will CorePower Yoga Teachers Actually Go on Strike? - Schriefer, Natalie (Yoga Journal, 2026)
As February 1 draws closer, everyone is asking this question. Here's everything you need to know.

There's a Specific Type of Grief We Don't Talk About. Yoga Can Help You Process It. - Schriefer, Natalie (Yoga Journal, 2026)
Give yourself permission to feel everything.
Keywords: dept.hhs

’Backrooms’ Tests the Future of Horror Movies - Schriefer, Natalie (Bloomberg.com, 2026)
The film may determine how much Hollywood is willing to bet on other stories without a clear monster.
Keywords: A24; Backrooms; Bloomberg Graphics; Hollywood; Theater; culture; dept.hhs; gaming; graphic; indie games; internet; movies; opinion column

Re-Playing Majora’s Mask, College - Schriefer, Natalie (Medium, 2026)
The guard who calls you a child eventually recants.
Keywords: dept.hhs

Komi Can't Communicate: Making Friends and Not Scaring People - Oda, Tomohito; Schriefer, Natalie (2026)
Learn to make friends and stop scaring people away with this clever book inspired by the hit manga Komi Can’t Communicate.Do you find it hard to sp...